2012
DOI: 10.3109/00365599.2012.721393
|View full text |Cite
|
Sign up to set email alerts
|

High-intensity focused ultrasound in prostate cancer: Today's outcomes and tomorrow's perspectives

Abstract: High-intensity focused ultrasound (HIFU) is a minimally invasive therapy applied for prostate cancer that capitalizes on the coagulation necrosis that occurs at temperatures greater than 60°C. Owing to a lack of long-term follow-up data the procedure is still considered experimental treatment. As primary therapy, HIFU is indicated in patients aged ≥70 years with clinical organ-confined disease, although it has also been used, with encouraging results, as first line salvage therapy after definitive treatment, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…The complications of cryotherapy are common but modest, mainly lower urinary tract obstruction and erectile dysfunction. The complication of HIFU included urine retention, need for subsequent TURP and urethral stricture (19). This technology still needs more research and long-term data to show its clinical efficacy and therapeutic role.…”
Section: Introductionmentioning
confidence: 99%
“…The complications of cryotherapy are common but modest, mainly lower urinary tract obstruction and erectile dysfunction. The complication of HIFU included urine retention, need for subsequent TURP and urethral stricture (19). This technology still needs more research and long-term data to show its clinical efficacy and therapeutic role.…”
Section: Introductionmentioning
confidence: 99%
“…Others have reported similar data [42]. Palermo et al reported the following adverse events, urinary retention in 1-9%, urethral structure in 4-14%, urinary incontinence in 1-15%, erectile dysfunction in 13-53% and rectourethral fistulae in 0-3% of patients [43]. A multicenter prospective investigation has also been designed as a medium-term (36 months) follow-up trial (The INDEX study) for assessment of biopsy outcomes to focal HIFU therapy in men with low-intermediate prostate cancer (PSA<15 ng/ml, Gleason <7, T2cN0M0)[44].…”
Section: Focal Therapy Of Localized Prostate Cancermentioning
confidence: 69%
“…Nanoparticle delivery has been shown to augment gene expression in a sitespecific manner in preclinical studies for a variety of tumors, including brain cancer [86], prostate cancer [87], hepatocellular carcinoma [88], pancreatic cancer [89], and kidney cancer [90]. Viral vectors are efficient but have undesired biolocalization problems.…”
Section: Gene Therapy For Specific Applicationsmentioning
confidence: 99%